Invasive candidiasis: investigational drugs in the clinical development pipeline and mechanisms of action. (3rd August 2022) - Hoenigl, Martin; Sprute, Rosanne; Arastehfar, Amir; Perfect, John R.; Lass-Flörl, Cornelia; Bellmann, Romuald; Prattes, Juergen; Thompson, George R.; Wiederhold, Nathan P.; Al Obaidi, Mohanad M.; Willinger, Birgit; Arendrup, Maiken C.; et al.
ABSTRACT: Introduction: The epidemiology of invasive Candida infections is evolving. Infections caused by non- albicans Candida spp. are increasing; however, the antifungal pipeline is more promising than ever and is enriched with repurposed drugs and agents that have new mechanisms of action. Despite progress, unmet needs in the treatment of invasive candidiasis remain, and there are still too few antifungals that can be administered orally or that have CNS penetration. Areas covered: The authors shed light on those antifungal agents active against Candida that are in early- and late-stage clinical development. Mechanisms of action and key pharmacokinetic and pharmacodynamic properties are discussed. Insights are offered on the potential future roles of the investigational agents MAT-2203, oteseconazole, ATI-2307, VL-2397, NP-339, and the repurposed drug miltefosine. Expert opinion: Ibrexafungerp and fosmanogepix have novel mechanisms of action and will provide effective options for the treatment of Candida infections (including those caused by multiresistant Candida spp). Rezafungin, an echinocandin with an extended half-life allowing for once weekly administration, will be particularly valuable for outpatient treatment and prophylaxis. Despite this, there is an urgent need to garner clinical data on investigational drugs, especially in the current rise of azole-resistant and multidrug-resistant Candida spp.